Cellular senescence in hepatocytes contributes to metabolic disturbances in NASH - Bonnet, Laurianne; Alexandersson, Ida; Baboota, Ritesh K.; Kroon, Tobias; Oscarsson, Jan; Smith, Ulf; Boucher, Jeremie (Frontiers in Endocrinology, 2022)
Cellular senescence is a state of irreversible cell cycle arrest and has been shown to play a key role in many diseases, including metabolic diseases. To investigate the potential contribution of hepatocyte cellular senescence to the metabolic derangements associated within the development of non-alcoholic steatohepatitis (NASH), we treated human hepatocyte cell lines HepG2 and IHH with the senescence-inducing drugs nutlin-3a, doxorubicin and etoposide. The senescence-associated markers p16, p21, p53 and beta galactosidase were induced upon drug treatment, and this was associated with increased lipid storage, increased expression of lipid transporters and the development of hepatic steatosis. Drug-induced senescence also led to increased glycogen content, and increased VLDL secretion from hepatocytes. Senescence was also associated with an increase in glucose and fatty acid oxidation capacity, while de novo lipogenesis was decreased. Surprisingly, cellular senescence caused an overall increase in insulin signaling in hepatocytes, with increased insulin-stimulated phosphorylation of IR, Akt, and MAPK. Together, these data indicate that hepatic senescence plays a causal role in the development of NASH pathogenesis, by modulating glucose and lipid metabolism, favoring steatosis. Our findings contribute to a better understanding of the mechanisms linking cellular senescence and fatty liver disease and support the development of new therapies targeting senescent cells for the treatment of NASH.